ENHANCEMENT OF THERAPEUTIC WINDOW OF METFORMIN HYDROCHLORIDE BY FABRICATION OF MICROSPHERES COMPRISING POLYMERIC INCULCATION WITH SEMI-SYNTHETIC AND SYNTHETIC POLYMERS BY IMPLEMENTATION OF BOX-BEHNKEN DESIGN - QUAZI, MD AAMER; KHANAM, NAZIA (International Journal of Applied Pharmaceutics, 2021)
Objective: Innovative enhancement of therapeutic window of Metformin hydrochloride (MFH) and bioavailability through mucoadhesive microspheres by polymeric inculcation of hydroxypropyl methylcellulose K4M grade (HPMC K4M), hydroxypropyl methylcellulose K100M grade (HPMC K100M) and Kollidon SR grade (KS). Methods: Controlled release system was developed by incorporating semi-synthetic and synthetic polymers by modified solvent evaporation technique. Fabrication of mucoadhesive microspheres was designed by the implementation of experimental designs to obtain most optimum concentration of selected factors. The method was optimized by Box Behnken design (BBD) with selected factors as concentrations of semi-synthetic and synthetic polymer with stirring speed influence for the obtained responses that were mean particle size (Y1) entrapment efficiency of drug (Y2) and percent mucoadhesion (Y3). Microspheres were characterized for particle size, entrapment efficiency of drug, ex-vivo mucoadhesion study, in vitro study, Fourier transform infrared spectroscopy (FTIR), x-ray diffraction (XRD) detection and H1 Nuclear magnetic resonance (NMR) quantification for optimized formulation. Results: Implementation of response surface method software for BBD yielded stable microspheres with mean particle size 274 µm, entrapment efficiency of drug 85.07% and percent mucoadhesion 67.03% for optimized formulation F5. Conclusion: Bridging of MFH with the highly innovative combination of semi-synthetic and synthetic polymers yielded stable, cost-effective microspheres with improved bioavailability with controlled-release effect as till date no literature is available that provide information with selected polymeric combination and analytical characterization.